Detection of Equus caballus Papillomavirus in Equine Aural Plaque Samples - Bromberger, Cristiana R. [UNESP] (2023)
Aural plaques have been linked to Equus caballus papillomavirus (EcPV). Ten types of EcPVs have already been described; however, only EcPVs 1, 3, 4, 5, and 6 have been observed in association with aural plaques. Accordingly, the objective of this study was to evaluate the presence of EcPVs in equine aural plaque samples. A total of 29 aural plaque samples (from 15 horses) were collected and assessed for the presence of the DNA of these EcPVs by PCR. Additionally, 108 aural plaque samples used in previous research were evaluated for the presence of EcPVs 8 and 9. Previously described primers were used for PCR to detect EcPVs 1 to 8, and specific primers were designed for EcPV 9. Minigenes were synthesized and used as a positive control in the PCRs for the undetected EcPVs. EcPVs 2, 7, 8, and 9 were not detected in any of the evaluated samples, suggesting that these viral types are not involved in the etiology of the equine aural plaque in Brazil. EcPV 6 was the most prevalent (81%), followed by EcPVs 3 (72%), 4 (63%) and 5 (47%), which reinforces the idea that these viruses play an important role in the etiology of the equine aural plaque in Brazil.